Development and Validation of a Combined RT-LAMP Assay for the Rapid and Sensitive Detection of Dengue Virus in Clinical Samples from Colombia - Leidy Hurtado-Gómez; Katherine Escorcia-Lindo; Juan Sebastian Rosero; Nataly Solano Llanos; Camilo Barrios Sánchez; Anderson Díaz Pérez; Yirys Díaz-Olmos; Jennifer García; Yesit Bello-Lemus; Leonardo C. Pacheco-Londoño; Antonio J. Acosta Hoyos; Lisandro A. Pacheco-Lugo (Diagnostics)
Background: Dengue virus (DENV) infection is a significant public health concern in several tropical and subtropical regions, where early and rapid detection is crucial for effective patient management and controlling the spread of the disease. Particularly in resource-limited, rural healthcare settings where dengue is endemic, there exists a need for diagnostic methods that are both easy to perform and highly sensitive. Objective: This study focuses on the development and validation of a single-tube reverse transcription loop-mediated isothermal amplification termed TURN-RT-loop-mediated isothermal amplification (LAMP) for the detection of DENV. Methodology: The TURN-RT-LAMP assay designed in this study combines two sets of primers targeting the 5′- and 3′-UTR of DENV, with the aim to increase the sensitivity of detection. Results: Clinical validation of the TURN-RT-LAMP assay using samples collected from febrile individuals with a serological or antigenic diagnosis revealed a sensitivity of >96%. The performance of this assay was statistically compared with that of the standard diagnostic method, quantitative reverse transcription-polymerase chain reaction. Conclusions: The results support the potential of RT-LAMP as a rapid, sensitive, and specific tool for the diagnosis and surveillance of dengue, particularly suitable for field use in low-resource settings.